REMEDIASI MISKONSEPSI PESERTA DIDIK PADA MATERI GERAK LURUS BERATURAN DENGAN BERBANTUAN MEDIA PEMBELAJARAN E-LEARING. - Wahyuni, Novi Sri; Maria S, Haratua Tiur; Hidayatullah, Muhammad Musa Syarif (Universitas Tanjungpura, 2023)
This study aims to investigate the remediation of students on the material of uniform motion with the help of e-learning learning media. This research is a descriptive qualitative research. This research was conducted at SMP Negeri 5 Selakau. The sample in this study amounted to 20 students. The data collection technique was carried out by giving tests that were carried out through elearning, namely google classroom, namely posttest and pre-test with 10 questions with open reasons to class VIIIA students. The data analysis of this research was carried out by means of data reduction, data presentation, and drawing conclusions. The results showed that the results of the pre-test and post-test. The mean score shows the results (0.7104) at the time of calculation, while based on the effect size formula (6.80), it is categorized as high in uniform straight motion material. So it is hoped that the results of this study can help students in overcoming misconceptions about the material of uniform straight motion in the learning outcomes of students in class VIIIA SMP Negeri 5 Selakau can be achieved in accordance with the learning objectives.